Application of mobile devices within distributed simulation-based decision making. (2017) - Brozek, Josef; Jakes, Martin
As a consequence of the development of the market with information technology, where users are increasingly inclined towards mobile devices at the expense of conventional stand-alone device, increasing user literacy in the use of smartphones and tablets and the increasing computing performance of mobile devices, a study has been created that addresses the potential of using mobile devices in a distributed simulation. The study also focuses on the possibility of applying the various technologies and architectures in context of using mobile devices in simulation. This article provides overview information about the case study itself, but it strongly focuses on technologies and paradigms that were identified as highly perspective. The paper also explains fundamental themes so that the readers could also apply the information in their home environment. Part of the work itself is an extensive case study carried out in collaboration with a commercial entity.